Nucleic acids and proteins carried by exosomes from various sources: Potential role in liver diseases - Xie, Danna; Qian, Baolin; Li, Xun (Frontiers in Physiology, 2022)
Exosomes are extracellular membrane-encapsulated vesicles that are released into the extracellular space or biological fluids by many cell types through exocytosis. As a newly identified form of intercellular signal communication, exosomes mediate various pathological and physiological processes by exchanging various active substances between cells. The incidence and mortality of liver diseases is increasing worldwide. Therefore, we reviewed recent studies evaluating the role of exosomes from various sources in the diagnosis and treatment of liver diseases.